Zasady odpowiedzialności majątkowej za szkody spowodowane wykonaniem decyzji organu sprawującego nadzór nad przedsiębiorstwem państwowym - Wostal, Mirosław (Wydział Prawa i Administracji UAM, 1987)
The article presents a special type of administrative-legal responsibility based on provisions defining the ways of compensating for damages caused to a state enterprise by legal acts of a supervisory organ. In the past, depending on the system of the management of the economy in force, the responsibility of such a kind was regulated in various ways and inadequately. To some extent, the present Act of September 25, 1981 on State Enterprises may further the regulation of the above issue. The Act defines the division of competences between a state organ and an enterprise; it must be decisive for the responsibility for undertaken decisions. Besides, the provisions of Art. 58 sec. 1-3 of the Act introduce a new very important principle according to which in case of damage resulting from carring out the decision of a supervisory organ, an enterprise may demand compensation from that organ. The above regulation is to increase the self-dependence of an enterprise and to protect it from economically detrimental decisions of a supervisory organ, irrespective of whether they are legal. One may also perceive in the above regulation the elements of prevention or warning to a supervisory organ, ordering it to concider the economic usefulness of undertaken decisions and their consequences for a self-dependent (legally and economically) enterprise. So far, however, there have been no suits for damages resulting from carring out a decision of a supervisory organ. Compensation may be claimed from an organ which issued a decision. Most often it is a founding organ and usually an organ of State administration. The damage must result from carring out the decision of a supervisory organ. The claim for compensation may be filed both by a director of an enterprise and by the employees' council; the competence of the latter results from the fact that the self-management organs are considered not only the organs of he factory crew but also the organs of an enterprise. The jurisdiction in suits for compensation for damages is vested usually in the provincial common court of law. The Act is silent as to the financial sources of compensation. One of the solutions might be to create a special fund for that purpose. At present, the plaintiffs should institute actions against the Treasury. By virtue of Art. 58 of the Act, the problem of vindicating the compensation has been regulated differently by orders of the Council of Ministers of September 30, 1981 with respect to state enterprises to which some parts of the Act do not apply.
The principles of pecuniary responsibility for damages caused by carrying out the decisions of an organ supervising the state enterprise